Sphingosine-1-phosphate alleviates colitis by regulating macrophage polarization and PI3k-Akt signaling - Hu, Liang; Yang, Zi; Zhang, Ying; Du, Conglin; Yang, Yang; Chang, Zhichao; Li, Xiangchun; Shan, Zhaochen (Frontiers in Immunology, 2025)
IntroductionInflammatory bowel disease (IBD) is a complex disease that is characterized by tight junction loss and dysregulation of immune homeostasis. The repair of intestinal integrity and immune function in IBD remains a clinical challenge. Sphingosine-1-phosphate (S1P) has been reported to alleviate radiation-induced salivary gland damage by maintaining epithelial integrity. However, its potential to restore function during IBD has not yet been investigated.MethodsDextran sulfate sodium (DSS) was added to the drinking water of C57BL/6 mice for 5 days to induce colitis. Subsequently, S1P and vehicle were injected intravenously on days 1, 3, and 5. Body weight, the disease activity index (DAI), and the histological activity index (HAI) were recorded. The level of apoptosis and expression of tight junction proteins among the groups were compared. We explored the underlying mechanisms of S1P using RNA sequencing.ResultsS1P alleviated DSS-induced colitis by suppressing inflammatory cell infiltration, reducing ulcers, and maintaining intestinal epithelial junction integrity by increasing E-cadherin and occludin expression. S1P decreased apoptosis, suppressed M1 macrophage polarization and promoted M2 macrophage polarizaion. RNA sequencing revealed upregulation of the phosphatidylinositol 3-kinase/protein kinase B (PI3K-Akt) and chemokine signaling pathways in the DSS group compared with those in the S1P group.ConclusionsS1P alleviated colitis by maintaing the intestinal epithelial integrity, promoting the polarization of M2 macrophage, suppressing chemokines, and regulating PI3K/Akt signaling pathway.